Pengaruh Kualitas Penduduk Dan Pembangunan Ekonomi Di Suatu Daerah Untuk Meningkatkan Perekonomian Masyarakat - Khairina Tambunan; M.E.I Arfan Tanjung; Muhammad Fawwaz Eljawahir Hsb; Achmad Al Hafiz Lubis (CV. ITTC INDONESIA, 2022)
An increase in load actually has several factors that can maintain a dynamic balance between the two. Forces that increase or decrease population. The aim of economic development is to improve people's standard of living and Distribution of income for the community. Population size plays an important role economic growth. Population is the number of people living in an area Of course, at certain times. Population is usually associated with growth (income per inhabitant), which roughly reflects the country's economic development. The method of this type of research is to use research based on analysis of literature reviews and qualitative methods from several journal sources that discuss population development, development and the community's economy based on the research that has been carried out. The purpose of this study is to find out how big the factors of infrastructure development are in better economic development.